Analysis on the Difference of Micropore Structure Characteristics and Physical Properties of Mixed Rock Reservoir. (19th April 2023) - Chen, Jinghua; Dong, Fengjuan; Yuan, Dongjiao; Zhou, Jiayi; Ding, Xiaojun; Bai, Jinlian; Zhao, Haizhu; Lu, Xuefei
Abstract : The accumulation of multiple source components leads to the superposition of multiple pore throat systems and similar pore throat distribution may correspond to different seepage capacity in the mixed rock reservoir. Taking the mixed rock reservoir of III+IV oil formation in Nanyishan Oilfield, Chaidamu Basin, as an example, the development characteristics of pore throat system and its controlling factors in the mixed rock were summarized by means of thin slice, scanning electron microscopy, X-ray diffraction and high pressure mercury injection, and the reservoir physical property differences and their genetic controlling mechanism were analyzed. The results show that the reservoir space of the mixed reservoir mainly consists of intergranular pore fracture, micropore fracture, and micropore-dissolution pore. The diverse and complex pore types make the reservoir space combination type, capillary pressure curve shape and reservoir physical properties are not completely corresponding. The higher the content of brittle minerals, the higher the reservoir permeability. However, the development of iron dolomite mainly destroys the reservoir. The permeability of reservoir is mainly controlled by the development degree of macropores and the pore size which is the main contribution to permeability, and the proportion of macropores increases with the increase of permeability.